Implementation of Civil Service Human Resource Management Policies and Their Impact on Government Organizational Productivity in Indonesia - Herling, Herling (Universitas Negeri Makassar, 2023)
The study explores the critical role of civil service human resource management policies in shaping the productivity of government organizations in Indonesia. In recent years, the effectiveness of these policies has garnered attention as governments strive to enhance efficiency and performance. The research aims to understand the direct and indirect impacts of these management policies on organizational productivity within the public sector. Using a qualitative research approach, the study involves in-depth interviews with key stakeholders, including policymakers, HR managers, and civil servants, to gather insights into the implementation process, challenges faced, and outcomes observed. Data were analyzed through thematic analysis to identify patterns and draw meaningful conclusions. The findings reveal that while the implementation of HR management policies has led to some improvements in organizational productivity, significant challenges remain, particularly in areas such as policy consistency, employee motivation, and resource allocation. These issues often stem from gaps in communication and a lack of tailored approaches to different organizational contexts. The study highlights the need for continuous evaluation and adaptation of HR policies to better align with the dynamic needs of government organizations, ensuring sustainable productivity gains. The research contributes to the broader discourse on public sector management by providing practical recommendations for enhancing the effectiveness of HR policies in the Indonesian civil service.